2016
DOI: 10.1111/jwas.12263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Dietary Inclusion of Hydrolyzed Soy Protein on the Growth, Nutrient Retention, Body Composition, and Serum Hormone of Juvenile Starry Flounder, Platichthys stellatus

Abstract: Enzymatic hydrolysis of soy protein has the potential to be an excellent protein source in marine fish feeds. Here we assessed the effects of different inclusion levels of hydrolyzed soy protein (HSP) on growth performance, nutrient retention, body composition, and serum hormone levels in juvenile starry flounder to define HSP utilization. Five isoenergetic and isoprotein diets were formulated with 0 (control), 10, 20, 30, and 40% HSP (SP10-40) to replace 0, 25, 50, 75, and 100% soy protein concentrate (SPC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The inclusion of a 27% of soybean and cotton hydrolysate mixture to replace fishmeal in Scophthalmus maximus diets increased the protein efficiency ratio (Song et al, 2018). Furthermore, enzymatic hydrolysis increases protein retention, which reduces environmental pollution caused by nitrogen compounds (Fang et al, 2017;Song et al, 2018;Song, Wang, Qiao, Zhang, & Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a 27% of soybean and cotton hydrolysate mixture to replace fishmeal in Scophthalmus maximus diets increased the protein efficiency ratio (Song et al, 2018). Furthermore, enzymatic hydrolysis increases protein retention, which reduces environmental pollution caused by nitrogen compounds (Fang et al, 2017;Song et al, 2018;Song, Wang, Qiao, Zhang, & Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These findings point to the important role of dietary peptides in appetite regulation. Previous reports also showed that the supplementation of peptides from hydrolyzed porcine mucosa, shrimp hydrolysate, and hydrolyzed soy protein increased the growth performance of broilers, sea breams, and starry flounders, respectively. These results demonstrated that among dietary N forms, peptides are critical for increasing feed intake and body weight gain.…”
Section: Discussionmentioning
confidence: 47%
“…While already a diverse food production sector, the ongoing research on aquaculture of many new species will likely result in even greater numbers of aquatic species in commercial production by 2050. Recent examples in the Journal of the World Aquaculture Society ( JWAS ) on culture techniques for species that are newer candidates for commercial production include: seahorses (Martínez‐Cardenas and Purser ; Qin et al ; Wang et al ), knifejaw (Biswas and Takii ), Chu's croaker (Huang et al ), crappie (Culpepper and Allen ), peppermint shrimp (Calvo et al ), spotted ivory shell (Lü et al ), painted river prawn (Gomes et al ), rabbitfish (Pham and Le ), and starry and southern flounder (Hu et al ; Song et al ).…”
mentioning
confidence: 99%